APA GUIDELINES FOR THE EVALUATION OF DEMENTIA AND AGE-RELATED COGNITIVE CHANGE: OVERVIEW AND CLINICAL APPLICATION. (20th December 2022) - Mast, Benjamin; Lichtenberg, Peter
Abstract: Dementia is a leading cause of cognitive and functional decline and the number of people living with dementia or involved in caring for another person with dementia continues to rise. There is a growing need for health professionals who are well trained in dementia assessment and intervention. In 2021, the American Psychological Association and its Committee on Aging (CONA) published a revision of the APA Guidelines for the Evaluation of Dementia and Age-Related Cognitive Change with the goal of promoting proficiency and expertise in this growing practice area. This symposium presents an overview of the APA Guidelines and their clinical application in various practice situations and settings. The first presentation (Mast) provides an overview of the guidelines and highlights areas of significant revision, including greater attention to multicultural competence, person-centered principles, and assessment of family caregivers. The second presentation (Steffen) presents the application of the APA Guidelines to working with older adults before formal assessment and diagnosis has been initiated. The third presentation (Allen) describes use of the APA Guidelines in the post-evaluation period and integrates GSA's revised KAER Toolkit for Primary Care Teams. The final presentation (Bush) presents ethical considerations before, during, and after dementia assessment.